CACHEXIA IN LUNG CANCER PATIENTS AT MILITARY HOSPITAL 103 AND SOME ASSOCIATED FACTORS - Phạm, Đức Minh (Tạp chí Dinh dưỡng và Thực phẩm, 2024)
Aims: The study aimed to evaluate the cachexia status and its associated factors in lung cancer patients. Methods: The cross-sectional study was conducted on 97 lung cancer in patients at the Oncology Center, Military Hospital 103, between 2020 and 2021. Results: The prevalence of cachexia in the lung cancer patients was 46.4%. In the multivariable regression models, the factors significantly associated with cachexia included age over 60 years (OR=3.3; p <0.05), NIS symptoms score (OR=1.26; p <0.01), and BMI <18.5 kg/m2 (OR=11.4; p <0.01). The NIS score demonstrated the best ability to screen for cachexia (AUC=0.715; p <0.001) in the lung cancer patients. Among the models combining factors for classifying cachexia, the Model consisted of 4 factors: NIS, BMI < 18.5 kg/m2, male gender, and age ≥ 60, yielding the best diagnostic value (AUC = 0.845; p < 0.001). Conclusions: Malnutrition was common among lung cancer patients. Age, BMI, and NIS score were significantly associated with cachexia. The combination of the associated factors could improve the discrimination of cachexia in lung patients.